The Venom of the Ectoparasitoid Wasp Pachycrepoideus vindemiae (Hymenoptera: Pteromalidae) Induces Apoptosis of Drosophila melanogaster Hemocytes - Wan, Bin (Insects, 2020)
The pupal ectoparasitoid Pachycrepoideus vindemiae injects venom into its fly hosts prior to oviposition. We have shown that this venom causes immune suppression in Drosophila melanogaster pupa but the mechanism involved remained unclear. Here, we show using transgenic D. melanogaster with fluorescent hemocytes that the in vivo number of plasmatocytes and lamellocytes decreases after envenomation while it has a limited effect on crystal cells. After in vitro incubation with venom, the cytoskeleton of plasmatocytes underwent rearrangement with actin aggregation around the internal vacuoles, which increased with incubation time and venom concentration. The venom also decreased the lamellocytes adhesion capacity and induced nucleus fragmentation. Electron microscopy observation revealed that the shape of the nucleus and mitochondria became irregular after in vivo incubation with venom and confirmed the increased vacuolization with the formation of autophagosomes-like structures. Almost all venom-treated hemocytes became positive for TUNEL assays, indicating massive induced apoptosis. In support, the caspase inhibitor Z-VAD-FMK attenuated the venom-induced morphological changes suggesting an involvement of caspases. Our data indicate that P. vindemiae venom inhibits D. melanogaster host immunity by inducing strong apoptosis in hemocytes. These assays will help identify the individual venom component(s) responsible and the precise mechanism(s)/pathway(s) involved.